How do I go about simplifying this equation? (Using i = \sqrt{-1}) [tex]\sqrt{-3}\cdot \:2i\sqrt{8}\left(-2\right)\sq

Question

How do I go about simplifying this equation? (Using i = \sqrt{-1})

\sqrt{-3}\cdot \:2i\sqrt{8}\left(-2\right)\sqrt{-2}i^{88}

in progress 0
Faith 2 weeks 2021-09-09T11:47:59+00:00 1 Answer 0

Answers ( )

    0
    2021-09-09T11:49:47+00:00

    Answer:

      16i√3

    Step-by-step explanation:

    I would write the radicals of negative numbers in terms of i, combine factors outside the radicals and combine factors inside the radicals. The power of i can be rewritten as a power of a power.

      =i\sqrt{3}\cdot 2i\sqrt{8}(-2)i\sqrt{2}\cdot i^{88}\\\\=(2)(-2)\sqrt{(3)(8)(2)}\cdot i^{91}\\\\=-4\sqrt{48}\cdot (i^2)^{45}\cdot i\\\\=-16\sqrt{3}(-1)^{45}\cdot i\\\\=16i\sqrt{3}

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )